The Effect of Field Dodder (Cuscuta campestris Yunck.) on Morphological and Fluorescence Parameters of Giant Ragweed (Ambrosia trifida L .) (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2013)
The effect of the parasitic flowering plant known as field dodder (Cuscuta campestris Yunck.) on morphological and fluorescence parameters of infested giant ragweed (Ambrosia trifida L.) plants was examined under controlled conditions. The parameters of chlorophyll fluorescence (Fo, Fv/Fm, ΦPSII, Fv, Fm, ETR and IF) were measured on infested (I) and non-infested (N) A. trifida plants over a period of seven days, beginning with the day of infestation. Morphological parameters (plant height, dry and fresh weight) were measured on the last day of fluorescence measurements.  C. campestris was found to affect the height, fresh and dry weight of the infested A. trifida plants, causing significant reduction in plant height and dry weight. Field dodder also affected several parameters of chlorophyll fluorescence (Fo, Fv/Fm, ΦPSII and Fv) in infested A. trifida plants.
Keywords: Cuscuta campestris; Ambrosia trifida; Morphology; Fluorescence